Chemoproteomic fishing identifies arzanol as a positive modulator of brain glycogen phosphorylase. Issue 91 (30th October 2018) - del Gaudio, Federica; Pollastro, Federica; Mozzicafreddo, Matteo; Riccio, Raffaele; Minassi, Alberto; Monti, Maria Chiara
Abstract : Arzanol, a natural compound with an intriguing structure, fished out brain glycogen phosphorylase as its main target, promoting enzyme activity. Abstract : The interactome of arzanol was investigated by MS-based chemical proteomics, a pioneering technology for small molecule target discovery. Brain glycogen phosphorylase (bGP), a key regulator of glucose metabolism so far refractory to small molecule modulation, was identified as the main high-affinity target of arzanol. Competitive affinity-based proteomics, DARTS, molecular docking, surface plasmon resonance and in vitro biological assays provided molecular mechanistic insights into the arzanol–enzyme interaction, qualifying this positive modulator of bGP for further studies in the realm of neurodegeneration and cancer.